An overview of interactions between wildlife and forest illegalities in Cameroon. (1st December 2022) - Assembe-Mvondo, S.; Kan, A.
Illegal exploitation of wildlife and forest resources are part of transnational crime, in which Cameroon plays a part. A review of documentation, interviews with key experts, and collection of field data in the markets and ports of the Cameroon's three main cities enabled the gathering of information on connections and synergies between these two criminal acts. The empirical evidence presented in this study demonstrates a strong connection between the illegal wildlife trade and illegal logging in Cameroon. These two areas of criminal activity maintain synergies through bad governance, weakening of rule of law, mafia connections between the two groups' actors involved and sharing access routes. Both result in negative ecological and socio-economic impacts.